Development Study of Technology-Based Adaptive Learning Modules for Students with Special Needs - Masruroh, Umi; Firdaus, Rangga; Fitriawan, Hely; Yulianti, Dwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research aims to examine the development of effective technology-based adaptive learning modules to support the learning of students with special needs in the context of inclusive education. Using the Systematic Literature Review (SLR) method, this study identifies, evaluates and interprets evidence from previous research related to the development of adaptive modules. The results show that educational technology, particularly adaptive learning modules, has an important role in improving access and quality of education for students with special needs. The results show that educational technology, particularly adaptive learning modules, has an important role in improving access to and quality of education for students with special needs. Adaptive modules allow for the customization of learning materials, methods and pace according to students' individual needs, which can improve their learning effectiveness and learning outcomes. This training can improve teachers' understanding of interventions for students with special needs and help them design adaptive learning services. It is hoped that the results of this study can make a significant contribution to the development of inclusive education in Indonesia and improve the quality of education for students with special needs through the use of adaptive technology